Accessibility - Health Literacy - Health Information Interdisciplinary Approaches to an Emerging Field of Communication - Ahrens, Sarah; Schulz, Rebecca; Kröger, Janina; Fernández-Garrido, Sergio; Keller, Loraine; Rink, Isabel (Easy - Plain - Accessible, 2022)
Recent studies show that more than half of the German population have difficulties in accessing, understanding, appraising, and applying health information, thus giving accessibility in health communication new traction. This volume links research and practice in the areas of accessible communication, health information and health literacy. The articles focus on these fields from a methodological, text and/or user perspective. The authors examine how to improve accessibility of research methods and how to adapt existing methods to answer questions about accessibility of health information. They discuss accessibility of text types and link accessibility to individual, organisational and professional health literacy. Contributions also give insight to the implementation of Easy and Plain Language in health information. All articles stem from different fields: in bringing them together, this volume fosters interdisciplinary exchange to communicate accessible health information and methods to specific vulnerable target groups.